A Multicentre Retrospective Study of Fulvestrant Use and Efficacy in Advanced/Metastatic Breast Cancer. Issue 4 (April 2022) - Lerner, A.; Keshwani, K.; Okines, A.; Sanderson, B.; Board, R.E.; Flynn, M.; Sharkey, E.; Konstantis, A.; Roylance, R.; Hanna, D.; King, J.; Murphy, R.; et al.
Abstract: Aims: Fulvestrant is a selective oestrogen receptor (ER) degrader used in postmenopausal women with hormone receptor-positive advanced breast cancer. The study aim was to analyse demographics and outcomes of UK patients treated with fulvestrant monotherapy at nine representative centres. Materials and methods: Medical records of 459 patients with locally advanced or metastatic ER-positive, HER2-negative breast cancer treated with fulvestrant between August 2011 and November 2018 at nine UK centres were reviewed. Data were collated on demographics, progression-free survival, overall survival and disease response at first radiological assessment following fulvestrant initiation. Patients still alive by December 2018 were censored. Results: Data from 429 of the 459 patients identified were eligible for inclusion in the analysis. The median age was 69 (range 21–95) and 64% ( n = 275) had Eastern Cooperative Oncology Group performance status 0–1. Bone was the most commonly involved metastatic site (72%, n = 306). However, 295 (69%) patients had visceral involvement. Patients had received a median 2 (range 0–5) prior lines of endocrine therapy and median 0 (range 0–6) prior chemotherapies. Fulvestrant was first-line therapy in 43 patients (10%). The median duration of treatment was 5 months (range 1–88). The median progression-free survival was 5.5 months. In 51% of 350 patients radiologically assessed, there was evidence of disease response to fulvestrant. Fifteen per cent of these had a complete/partial response. Fulvestrant was discontinued predominantly due to disease progression, with 3% discontinued solely due to adverse events. The median overall survival for the whole cohort was 22.5 months (range 0–88). Conclusions: This is one of the largest studied cohorts of breast cancer patients treated with fulvestrant. This heavily endocrine-pretreated population reflects real-life use in the UK. Within this context, our retrospective data show that patients can experience maintained disease response when treated with fulvestrant, supporting the importance of equitable availability for all UK patients. Highlights: Fulvestrant is licensed for the treatment of hormone receptor-positive advanced breast cancer in postmenopausal women. One of the largest studied patient cohorts treated with fulvestrant, with data collection from nine UK centres. Results confirm a modest radiological response rate even in a predominantly pretreated cohort. Fair access to fulvestrant monotherapy in England should be standard to enable its use in patients most likely to benefit.